Combined coagulation factor VIII and factor IX deficiency (CDF8F9) in a patient from Lithuania - Ivaškevičius, V.; Pezeshkpoor, B.; Biswas, A.; Goldmann, G.; Horneff, S.; Gimbutyte, M.; Malciute, L.; Jurgutis, R.; Oldenburg, J. (Hämostaseologie, 2016)
Haemophilia A (FVIII deficiency) and haemophilia B (FIX deficiency) are X-linked inherited bleeding disorders. It is a very rare event to identify both haemophilias in the same patient. So far, only two families with such combination are reported in the literature worldwide supported by genetic background. Patients and methods: Evaluation of clinical data, determination of FVIII and FIX levels and genetic analysis of F8 and F9 genes by direct sequencing. Results: We report on a patient having severe haemophilia B (FIX:C <1 IU dl-1) and mild haemophilia A (FVIII:C 18 IU dl-1 ). FIX deficiency was known since childhood, whereas mild haemophilia A was confirmed at the age of 42 due to unexpected bleeding complications after dental extraction despite adequate substitution with plasma derived FIX concentrate. F9 gene analysis showed a point mutation in exon 2 (c.223C>T, p.R75X), whereas F8 gene analysis revealed a point mutation in exon 4 (c.545A>C, p.D182A). The mother of the patient was heterozygous for F8 mutation, but not for F9 mutation suggesting a de novo F9 mutation. Accidentally, further family from Germany with mild Haemophilia A was identified to have the same F8 mutation. F8 Haplo-type analysis revealed that the p.D182A mutation most likely represents a founder mutation with common ancestors of the German and the Lithuanian family. Conclusions: Our results confirm the rare event of Haemophilia A and haemophilia B in the same patient originating from two distinct genetic defects in F8 and F9 genes.
Keywords: Factor VIII; factor IX; haemophilia A and B; CDF8F9; founder mutation